Application of Extracorporeal Membrane Oxygenation in Patients With Severe Acute Respiratory Distress Syndrome Caused by Pneumocystis jirovecii Pneumonia Following Kidney Transplantation: A Case Series - Wang, Hong-Yu; Li, Yi-Hao; Zhang, Si-Sen; Jiang, Xin; Niu, Xing-Guo; Qian, Xin-Ling; Liu, Cong-Yan (Frontiers in Physiology, 2022)
Objective: To investigate the application effect of extracorporeal membrane oxygenation (ECMO) in patients with severe acute respiratory distress syndrome (ARDS) caused by Pneumocystis jirovecii pneumonia (PJP) after kidney transplantation. Methods: This is a case series on 10 kidney transplant recipients with severe ARDS caused by PJP at the People’s Hospital of Zhengzhou, who were enrolled as the case group. A total of 17 cases of PJP diagnosed with severe ARDS without ECMO were selected as the control group. The timing and mode of ECMO support and treatment complications were summarized. The primary aim of this study was mortality and secondary was imaging and complications. Results: The enrolled patients’ oxygenation index before the start of ECMO ranged from 25 to 92, and the time from admission to the start of ECMO was 1–17 days, with an average of 5.56 days. In the case group, one patient died of hemorrhagic shock due to abdominal hemorrhage, but the other nine patients were successfully weaned from ECMO. Of these patients, one died due to sepsis following weaning. The survival rate in the case group was 80.0% (8/10), and the survival rate in the control group was 35.29% (6/17). The vein–vein ECMO support time in the nine successfully weaned patients in the case group ranged from 131 to 288 hours, with an average of 215.5 hours. Of the eight patients who survived, deterioration of renal function after transplantation occurred in two patients, but no fatal complications occurred. Conclusion: Overall, Patients with severe ARDS caused by postoperative PJP infection following kidney transplantation have a poor prognosis. The mortality was lower in patients who were treated with ECMO compared to standard care.